Muscular strength development in children and adolescents - Beunen, G.; Thomis, M. (Pediatric Exercise Science, 2000)
This review builds on earlier reviews and considers the development of strength characteristics from childhood through adulthood. Since strength is associated with size and biological maturation, these associations are also discussed. Finally, genetic determinants of strength and tracking of strength components over time are also reviewed.